Amphiphilic polyelectrolyte composites, multilayers, and blends
By coating the copolymer of hydrophobic and charged repeating units on the porous support, forming a composite film, the problems of high energy consumption and poor scaling resistance during the membrane separation process are solved, and efficient and economical solute separation and water treatment are achieved. application.
Patent Information
- Application Number
- CN202380035506.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, there are problems such as high energy consumption, limited selectivity and poor anti-scaling during membrane separation, which limits the widespread application of membranes in high concentrations of biomacromolecules, particulate matter and oil, and conventional membrane materials. The complexity of synthesis and manufacturing limits its large-scale production.
The porous support is coated with a copolymer containing hydrophobic repeating unit and charged repeating unit to form a composite membrane, which adjusts the pore size and selectivity of the membrane through hydrophobicity and charge interaction, and improves anti-scattering and adjustability.
It achieves efficient solute separation, reduces energy consumption, improves the economic feasibility and anti-scaling properties of the membrane, simplifies the manufacturing process, and is suitable for a variety of filtration and water treatment applications.
Smart Images

Figure CN119233859A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 325,274, filed on March 30, 2022, the contents of which are hereby incorporated by reference in their entirety.
[0003] Government support
[0004] This invention was made with government support under Grant No. DEFE003185 awarded by the Department of Energy and Grant No. 1553661 awarded by the National Science Foundation. The government has certain rights in this invention. Background Art
[0005] One of the most energy-intensive activities in the chemical industry is separating chemical compounds. Membranes are excellent candidates for achieving efficient separations: they are scalable, energy-efficient, and have been widely used in gas and liquid separation processes. Nevertheless, their wider use is limited by the separation capacity, fouling, and stability of membranes prepared by conventional methods.
[0006] Currently, separation of molecules of similar size is achieved using energy-intensive methods such as chromatography, distillation and extraction. For example, the purification of propane and ethylene alone accounts for 0.3% of global energy consumption. Adopting membranes to perform these challenging separations instead of current methods would significantly reduce energy consumption while increasing the sustainability of these processes. Other separations, such as the separation of benzene derivatives from each other and the separation of bioactive compounds with added value, are potential processes that could use membranes.
[0007] In addition to selectivity limitations, membrane fouling will severely limit the wider use of membranes in applications where the feed has high concentrations of biomacromolecules, particulate matter and / or oil components. Therefore, it is critical to consider fouling protection when designing new membrane materials. Fouling is one of the most interesting research areas in membrane filtration and a major obstacle to improving the performance of membrane separation processes. 6 Fouling has a detrimental effect on membrane performance and integrity. Given the limitations of commercially available membranes in resisting fouling agents, the ability to tune membrane properties such as permeability, pore size, and selectivity while maintaining ease of manufacturability and high resistance to fouling could revolutionize the field of water filtration.
[0008] Finally, membranes with higher selectivity can improve the economic viability of membrane processes for many applications. For example, membranes with nanoscale tunable pore size and charge can be used in biological separations, treatment of complex wastewaters, selective removal of organics (e.g., dyes) and other contaminants from solutions for reuse, water softening, pretreatment of seawater for desalination by reverse osmosis (RO), and final treatment of secondary and tertiary wastewater effluents. In all of these cases, selectivity paired with fouling resistance is critical.
[0009] Previous studies have shown that random zwitterionic amphiphilic copolymer (r-ZAC) membranes can be formed by self-assembly of zwitterionic nanodomains, which act as an effective nanochannel network for water permeation. The main characteristics of r-ZAC membranes include excellent anti-fouling, a size cutoff of ~1-1.5nm, and low salt ion retention. However, although various zwitterionic monomers can be synthesized, only a few are commercially available, some of which are only available from one supplier. In addition, most zwitterionic monomers show poor solubility in many solvents, further increasing their synthetic challenges. Therefore, the range of r-ZAC chemicals that can be practically converted into large-scale membranes is limited. On the other hand, ionic or ionizable monomers are widely available, cheaper, and generally easier to dissolve and synthesize.
[0010] Another class of selective layers that have gained attention in the past decade are polyelectrolyte multilayers, which are constructed by layer-by-layer (LBL) deposition of oppositely charged polyelectrolytes. The multilayer approach allows the development of membranes based on the formation of polyelectrolyte complexes between multiple oppositely charged water-soluble homopolymers. Although these membranes have shown good membrane performance, especially in the removal of micropollutants, there are not many studies on their non-crosslinked long-term stability. In addition, their manufacturing methods require multiple steps and are complicated to scale up. These coatings are usually made by several rounds of alternating anionic and cationic, water-soluble polyelectrolytes, separated by rinsing. Usually at least 3-5 double layers are required (thus requiring 12-20 dip or spray steps). Summary of the invention
[0011] In one aspect, the present disclosure provides a composite membrane comprising a porous support; and a selective layer comprising a first copolymer and a second copolymer; wherein:
[0012] The first copolymer comprises a first plurality of hydrophobic repeating units and a plurality of cationic repeating units;
[0013] The second copolymer comprises a second plurality of hydrophobic repeating units and a plurality of anionic repeating units; and
[0014] The first copolymer and the second copolymer are substantially insoluble in water (eg, under operating conditions).
[0015] In another aspect, the present disclosure provides a method of separating a solute from a solution, comprising contacting the solution with a composite membrane disclosed herein.
[0016] In another aspect, the present disclosure provides a method of making a composite membrane disclosed herein, comprising applying a first copolymer as disclosed herein and a second copolymer as disclosed herein to a porous support, thereby making a composite membrane disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The NMR spectrum of the A+ chemical structure is shown, indicating copolymerization of two monomer units.
[0018] Figure 2 The NMR spectrum of the S-chemical structure is shown, indicating copolymerization of two monomer units.
[0019] Figure 3 Shown is a SEM image of SA coated on PS35.
[0020] Figure 4 The rejection of neutral dyes is shown for all films.
[0021] Figure 5 An S-curve using a neutral solute is shown.
[0022] Figure 6 The rejection rate of Na2SO4 at different concentrations is shown.
[0023] Figure 7 The rejection rate of Na2SO4 at different concentrations is shown.
[0024] Figure 8 The rejection rate of Na2SO4 at different concentrations is shown.
[0025] Fig. 9 The MgCl2 rejection rate at different concentrations is shown.
[0026] Fig.10 The MgCl2 rejection rate at different concentrations is shown.
[0027] Fig.11 The MgCl2 rejection rate at different concentrations is shown.
[0028] Fig.12 The NaCl rejection rate at different concentrations is shown.
[0029] Fig.13 The NaCl rejection rate at different concentrations is shown.
[0030] Fig.14The NaCl rejection rate at different concentrations is shown.
[0031] Fig.15 The 5-hour fouling test of oil-in-water for S- and SA is shown. The initial flux of these membranes was set to 10 L / m 2 .h.
[0032] Fig.16 The NMR spectrum of the M-chemical structure is shown, depicting the copolymerization of two monomer units.
[0033] Fig.17 Shown is a SEM image of AM coated on PS35.
[0034] Fig.18 Shown is a SEM image of 70 / 30 coated on PS35.
[0035] Fig.19 The water permeability of different APEC blend layers is shown.
[0036] Fig. 20 The vitamin B12 rejection rate using different APEC blend layers is shown.
[0037] Fig.21 The rejection rate of Na2SO4 at different concentrations is shown.
[0038] Fig. 22 The MgCl2 rejection rate at different concentrations is shown.
[0039] Fig.23 The NaCl rejection rate at different concentrations is shown.
[0040] Fig.24 The NMR spectrum of the A2+ chemical structure is shown, indicating copolymerization of two monomer units.
[0041] Fig.25 The NMR spectrum of the S-chemical structure is shown, indicating copolymerization of two monomer units.
[0042] Fig.26 Shown is a SEM image of A2S coated on PS35.
[0043] Fig. 27 The rejection of neutral dye by A2S, AS and control films is shown.
[0044] Fig.28 An S-curve using a neutral solute is shown.
[0045] Fig.29 The rejection rate of Na2SO4 at different concentrations is shown.
[0046] Fig.30 The MgCl2 rejection rate at different concentrations is shown.
[0047] Fig.31 The NaCl rejection rate at different concentrations is shown.
[0048] Fig.32 The NMR spectrum of the A+ chemical structure is shown, indicating copolymerization of two monomer units.
[0049] Fig.33 The NMR spectrum of the S2-chemical structure is shown, indicating copolymerization of two monomer units.
[0050] Fig.34 Shown is a SEM image of AS2 coated on PS35.
[0051] Fig.35 Shown are the rejection rates of neutral dyes by AS2, AS, and control films.
[0052] Fig.36 The rejection rate of Na2SO4 at different concentrations is shown.
[0053] Fig.37 The MgCl2 rejection rate at different concentrations is shown.
[0054] Fig.38 The NaCl rejection rate at different concentrations is shown. DETAILED DESCRIPTION
[0055] Thin Film Composite (TFC) membranes are disclosed wherein a thin "selective layer" is coated on a porous support, wherein the selective support comprises a combination of at least two copolymers:
[0056] 1) "Cationic copolymers" comprising at least two types of repeating units: hydrophobic repeating units whose homopolymers are insoluble in water, and cationic repeating units which are at least partially positively charged when in water,
[0057] 2) "Anionic copolymers" comprising at least two types of repeating units: hydrophobic repeating units as described above, and anionic repeating units which are at least partially negatively charged in water.
[0058] In certain preferred embodiments, both copolymers are substantially insoluble in water under the conditions of use. Typically, each copolymer contains ~5-80% by weight of charged (anionic or cationic) repeat units, more preferably 15-75% of charged repeat units, more preferably 30-60% of charged repeat units. This feature distinguishes this technology from, for example, polyelectrolyte multilayer coatings, which involve water-soluble polyelectrolytes that do not contain hydrophobic repeat units deposited from aqueous solutions.
[0059] In certain preferred embodiments, the average molar mass of the two copolymers may be at least 30,000 g / mol, more preferably greater than 50,000 g / mol, and even more preferably greater than 100,000 g / mol.
[0060] The two copolymers can be deposited onto a porous support to form a selective layer, for example, by one of the following two methods:
[0061] i) Each copolymer is coated sequentially onto a support, thereby creating at least one layer of anionic copolymer and one layer of cationic copolymer on the support. This family of membranes will be referred to hereinafter as "bilayer membranes", but in principle a higher number of layers is also possible.
[0062] ii) Creating a mixture or blend of the two copolymers by dissolving them in the same solvent and then coating the blend onto a support to create the selective layer. This family of membranes will be referred to as "blended membranes".
[0063] In each case, the effective pore size of the support membrane is significantly higher than that of the TFC membrane; the selective layer significantly alters the rejection properties of the support.
[0064] Exemplary hydrophobic repeating units include repeating units derived from: 2,2-trifluoroethyl methacrylate (TFEMA); other fluorinated acrylates, methacrylates, and acrylamides (e.g., pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, pentafluorophenyl methacrylate); styrene; methyl methacrylate; acrylonitrile; 2-chloroethyl methacrylate; 2-bromoethyl methacrylate; allyl methacrylate; other monomers that meet the above criteria. In addition, hydrophobic monomeric peptides or blocked amino acids that do not have ionizable / charged groups under the conditions of use can be used as hydrophobic monomeric units.
[0065] Exemplary anionic repeating units include repeating units derived from methacrylic acid (MAA); 2-sulfoethyl methacrylate (SEMA); L-tryptophan-methacrylamide; D-tryptophan-methacrylamide; L or D-tryptophan-acrylamide; L or D-alanine-methacrylamide; L or D-alanine-acrylamide; L or D-valine-methacrylamide; L or D-valine-acrylamide; L or D-isoleucine-methacrylamide; L or D-isoleucine L or D-amino acid-acrylamide; L or D-alloisoleucine-methacrylamide; L or D-alloisoleucine-acrylamide; L or D-methionine-methacrylamide; L or D-methionine-acrylamide; L or D-phenylalanine-methacrylamide; L or D-phenylalanine-acrylamide; L or D-tyrosine-methacrylamide; L or D-tyrosine-acrylamide; L or D-histidine-methacrylamide; L or D-histidine-acrylamide; L or D-glutamic acid-methacrylamide; L or D -Glutamic acid-methacrylamide; L or D-aspartic acid-acrylamide; L or D-aspartic acid-methacrylamide; acrylic acid; 2-carboxyethyl acrylate; mono-2-(methacryloyloxy)ethyl succinate; mono-2-(methacryloyloxy)ethyl maleate; sodium 4-vinylbenzenesulfonate; 2-acrylamido-2-methylpropanesulfonic acid; 2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt; 2-acrylamido-2-methyl-1-propanesulfonic acid; potassium 3-sulfopropylacrylate Salt; 3-sulfopropyl methacrylate potassium salt; 3-vinylbenzoic acid; 4-vinylbenzoic acid; 2-vinylbenzoic acid; 4-(2-propenyl)benzoic acid; 2-methyl-2-propene-1-sulfonic acid sodium salt; vinylsulfonic acid sodium salt; vinylphosphonic acid; (4-vinylphenyl)methylphosphonic acid; methacrylate, acrylate, methacrylamide, acrylamide, styrene or vinyl derivatives containing carboxylic acid, sulfonate, phosphate or other ionizable / charged groups that are negatively charged under the conditions of use. Monomeric peptides having ionizable / charged groups that are negatively charged under the conditions of use can also be used as anionic monomer units.
[0066] Exemplary cationic repeating units include repeating units derived from: [2-(methacryloyloxy)ethyl]trimethylammonium chloride (MAETA); [3-(methacrylamido)propyl]trimethylammonium chloride; [2-(acryloyloxy)ethyl]trimethylammonium chloride; (3-acrylamidopropyl)trimethylammonium chloride; 4-vinylbenzyl(triphenyl)phosphonium chloride; methacrylic acid (vinylbenzyl)trimethylammonium chloride; 3-vinylaniline; 4-vinylaniline; 2-isopropenylaniline; N-( 3-aminopropyl) methacrylamide hydrochloride; N-vinylimidazolium; 1-allyl-3-vinylimidazolium; 1-allyl-2methyl-5-vinylpyridinium; 1-allyl-5-vinylpyridinium; 1-methyl-1-(1-vinylcyclohexyl)pyrrolidinium iodide; methacrylate, acrylate, methacrylamide, acrylamide, styrene or vinyl derivatives containing amine, pyridinium, imidazolium, phosphonium, pyrrolidinium or other ionizable / charged groups that are positively charged under the conditions of use. Repeating units with strong cationic charges (e.g., quaternary amine groups) are preferred. In addition, monomeric peptides with ionizable / charged groups that are positively charged under the conditions of use can be used as cationic monomer units.
[0067] In certain embodiments, the films described herein include the following features:
[0068] i) Smaller effective pore size than the support
[0069] ii) Scalable Manufacturing
[0070] In certain embodiments, the membranes disclosed herein, such as bilayer membranes, include the following features:
[0071] • They exhibit smaller effective pore sizes than membranes prepared by coating only anionic copolymers or only cationic copolymers on the same support, as quantified by measuring the rejection of neutral solutes.
[0072] • Their water permeabilities are within the range of commercially available membranes with comparable effective pore sizes and can potentially be tuned higher.
[0073] They can be prepared using copolymers with essentially any pair of ionizable or charged groups (i.e., anionic and cationic) as long as they can be dissolved and coated. This is in contrast to blended membranes, where certain pairs of functional groups have very limited solubility and will coagulate when blended in solution, limiting the available options.
[0074] Without wishing to be bound by theory, it is believed that the selectivity of these membranes arises from a very thin layer at the interface of the two coating layers where the anionic copolymer and the cationic copolymer interact and create a tighter "network" than either copolymer alone.
[0075] The selectivity / effective pore size of these membranes can be controlled by the ratio of hydrophobic / charged monomers in each copolymer. In addition, the degree of interlayer mixing, which is affected by factors such as solvent selection, temperature, casting speed, external gas flow and post-treatment, may affect the effective pore size as well as the chemical nature of the charged group pairs.
[0076] • These membranes exhibit improved anti-fouling properties. For example, layers that are either completely mixed (ie, substantially homogeneous throughout the layer) or nearly completely mixed and nearly charge neutral are particularly resistant to fouling, similar to previously reported polyampholyte membranes.
[0077] Additionally, it is contemplated that bilayers can be designed to be cross-linkable, including at the interface (e.g., by reactions between anionic and cationic copolymers), thereby further providing stability and tunability. These reactions may include, for example, reactions between epoxides and primary amines or alcohols; reactions between alkyl halides and tertiary amines; reactions between azides and alkynes. This would require the presence of a third monomer unit in the polymer; and / or the presence of reactive groups in the charged monomer units and / or the hydrophobic monomer units.
[0078] In certain embodiments, the films disclosed herein, such as blended films, include the following features:
[0079] The effective pore size of the blend membranes is also smaller than that of the support, and is generally smaller than that of each individual copolymer, as quantified by measuring the rejection of neutral solutes. However, their effective pore size is generally larger than that of membranes prepared using the bilayer approach with the same copolymers.
[0080] Exhibits highly tunable effective pore size, which can be controlled by varying the molar ratio of anionic and cationic groups. This parameter can also control / variegate permeability and salt rejection.
[0081] • Resistance to fouling as compared to other membranes on the market, and those that are charge neutral or close to charge neutral will have particularly high resistance to fouling.
[0082] In certain embodiments, the films disclosed herein, such as bilayer and blend films, include the following features:
[0083] Easy and scalable copolymer synthesis.
[0084] • Easy, scalable fabrication of membranes with a broad and controlled selectivity range that can be tuned to achieve desired properties (e.g., salt rejection, softening, size-based separation of organic molecules, water treatment for selective removal of pollutants).
[0085] · Anti-scaling properties against a range of scale forming substances.
[0086] Chlorine resistance.
[0087] Chemical resistance.
[0088] In certain aspects, material systems and methods of making membranes with improved capabilities are described. In the past, the introduction of multilayer membranes with charged groups has focused only on water-soluble polyelectrolyte multilayers deposited by adsorption from water; the present invention describes rod coating of water-insoluble copolymers from organic solutions. The properties of the membranes are highly tunable and adaptable.
[0089] The membranes disclosed herein behave differently from polyelectrolyte multilayer membranes. The formation of tightly interwoven / composite layers at the interface of two separately deposited layers has not been reported in any other system.
[0090] The disclosed invention can be used in many filtration processes requiring size and charge selective separation, including water and wastewater treatment and nutrient separation and recovery.
[0091] In one aspect, the present disclosure provides a composite membrane comprising a porous support; and a selective layer comprising a first copolymer and a second copolymer; wherein:
[0092] The first copolymer comprises a first plurality of hydrophobic repeating units and a plurality of cationic repeating units;
[0093] The second copolymer comprises a second plurality of hydrophobic repeating units and a plurality of anionic repeating units; and
[0094] The first copolymer and the second copolymer are substantially insoluble in water (eg, under operating conditions).
[0095] In certain preferred embodiments, the first copolymer and the second copolymer are insoluble in water (eg, under operating conditions).
[0096] In certain embodiments, the composite membrane is a thin film composite membrane.
[0097] In certain embodiments, the composite film has a thickness of about 20 μm to about 1,000 μm. In certain embodiments, the composite film has a thickness of about 50 μm to about 200 μm.
[0098] In certain embodiments, the selective layer has a thickness of about 30 nm to about 5 μm. In certain embodiments, the selective layer has a thickness of about 30 nm to about 1,000 nm. In certain embodiments, the selective layer has a thickness of about 10 nm, about 25 nm, about 50 nm, about 75 nm, about 100 nm, about 125 nm, about 150 nm, about 175 nm, about 200 nm, about 225 nm, about 250 nm, about 275 nm, about 300 nm, about 325 nm, about 350 nm, about 375 nm, about 400 nm, about 425 nm, about 450 nm, about 475 nm, about 500 nm, about 525 nm, about 550 nm, about 575 nm, or about 600 nm. In certain embodiments, the selective layer has a thickness of about 400 nm, about 425 nm, about 450 nm, about 475 nm, about 500 nm, about 525 nm, about 550 nm, about 575 nm, or about 600 nm.
[0099] In certain embodiments, the plurality of cationic repeating units are partially positively charged in water (e.g., in water at a neutral pH or in water under operating conditions). In certain embodiments, the plurality of cationic repeating units are partially positively charged in water (e.g., in water at a neutral pH or in water under operating conditions).
[0100] In certain embodiments, the plurality of anionic repeating units are partially negatively charged in water (e.g., in water at a neutral pH or in water under operating conditions). In certain embodiments, the plurality of anionic repeating units are negatively charged in water (e.g., in water at a neutral pH or in water under operating conditions).
[0101] In certain embodiments, the selective layer consists essentially of the first copolymer and the second copolymer.
[0102] In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 5-80 % by weight. In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 15-75 % by weight. In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 30-60 % by weight. In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 10 % by weight, about 20 % by weight, about 30 % by weight, about 40 % by weight, about 50 % by weight, about 60 % by weight, about 70 % by weight or about 80 % by weight. In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 5-80 % by mole. In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 15-75 % by mole.
[0103] In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 5-80 mol %.In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 15-75 mol %.In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 30-60 mol %.In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 10 mol %, about 20 mol %, about 30 mol %, about 40 mol %, about 50 mol %, about 60 mol %, about 70 mol % or about 80 mol %.In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 5-80 mol %.In certain embodiments, the first copolymer comprises the multiple cationic repeating units of about 15-75 mol %.
[0104] In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 5-80 weight %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 15-75 weight %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 30-60 weight %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 10 weight %, about 20 weight %, about 30 weight %, about 40 weight %, about 50 weight %, about 60 weight %, about 70 weight % or about 80 weight %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 5-80 weight %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 15-75 weight %.
[0105] In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 5-80 mol %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 15-75 mol %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 30-60 mol %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 10 mol %, about 20 mol %, about 30 mol %, about 40 mol %, about 50 mol %, about 60 mol %, about 70 mol % or about 80 mol %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 5-80 mol %.In certain embodiments, the first copolymer includes the multiple first multiple hydrophobic repeating units of about 15-75 mol %.
[0106] In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 5-80 % by weight. In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 15-75 % by weight. In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 30-60 % by weight. In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 10 % by weight, about 20 % by weight, about 30 % by weight, about 40 % by weight, about 50 % by weight, about 60 % by weight, about 70 % by weight or about 80 % by weight. In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 5-80 % by mole. In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 15-75 % by mole.
[0107] In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 5-80 mol %.In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 15-75 mol %.In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 30-60 mol %.In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 10 mol %, about 20 mol %, about 30 mol %, about 40 mol %, about 50 mol %, about 60 mol %, about 70 mol % or about 80 mol %.In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 5-80 mol %.In certain embodiments, the second copolymer comprises the multiple anionic repeating units of about 15-75 mol %.
[0108] In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 5-80 weight %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 15-75 weight %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 30-60 weight %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 10 weight %, about 20 weight %, about 30 weight %, about 40 weight %, about 50 weight %, about 60 weight %, about 70 weight % or about 80 weight %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 5-80 weight %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 15-75 weight %.
[0109] In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 5-80 mol %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 15-75 mol %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 30-60 mol %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 10 mol %, about 20 mol %, about 30 mol %, about 40 mol %, about 50 mol %, about 60 mol %, about 70 mol % or about 80 mol %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 5-80 mol %.In certain embodiments, the second copolymer includes the multiple second multiple hydrophobic repeating units of about 15-75 mol %.
[0110] In certain embodiments, the first copolymer has an average molar mass of at least 50,000 g / mol. In certain embodiments, the first copolymer has an average molar mass of at least 100,000 g / mol. In certain embodiments, the first copolymer has an average molar mass of 20,000 g / mol to about 500,000 g / mol. In certain embodiments, the first copolymer has an average molar mass of 30,000 g / mol to about 500,000 g / mol. In certain embodiments, the first copolymer has an average molar mass of 50,000 g / mol to about 500,000 g / mol. In certain embodiments, the first copolymer has an average molar mass of 100,000 g / mol to about 500,000 g / mol.
[0111] In certain embodiments, the second copolymer has an average molar mass of at least 50,000 g / mol. In certain embodiments, the second copolymer has an average molar mass of at least 100,000 g / mol. In certain embodiments, the second copolymer has an average molar mass of 20,000 g / mol to about 500,000 g / mol. In certain embodiments, the second copolymer has an average molar mass of 30,000 g / mol to about 500,000 g / mol. In certain embodiments, the second copolymer has an average molar mass of 50,000 g / mol to about 500,000 g / mol. In certain embodiments, the second copolymer has an average molar mass of 100,000 g / mol to about 500,000 g / mol.
[0112] In certain embodiments, the first copolymer and the second copolymer are sequentially layered on a porous support (e.g., the first copolymer and the second copolymer are sequentially applied to a porous support). In certain embodiments, the first copolymer is the first layer (e.g., the outermost layer) and the second copolymer is the second layer (e.g., the first copolymer layer is on the second copolymer layer and the second copolymer layer is in contact with the porous support). In other embodiments, the second copolymer is the first layer (e.g., the outermost layer) and the first copolymer is the second layer (e.g., the second copolymer layer is on the first copolymer layer and the first copolymer layer is in contact with the porous support). In other embodiments, the first copolymer and the second copolymer are blended on a porous support (e.g., the first copolymer and the second copolymer form a homogeneous layer on the porous support).
[0113] In certain embodiments, the first plurality of hydrophobic repeating units comprises repeating units derived from acrylate (e.g., alkyl acrylate, fluorinated acrylate or methacrylate), acrylamide (e.g., fluorinated acrylamide), styrene or hydrophobic amino acids. In certain embodiments, the first plurality of hydrophobic repeating units comprises repeating units derived from methacrylate. In certain embodiments, the first plurality of hydrophobic repeating units comprises repeating units derived from methacrylate 2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl ester, pentafluorophenyl methacrylate, styrene, methyl methacrylate, acrylonitrile, 2-chloroethyl methacrylate, 2-bromoethyl methacrylate and allyl methacrylate. In certain preferred embodiments, the first plurality of hydrophobic repeating units comprises repeating units derived from methacrylate 2,2-trifluoroethyl ester (TFEMA).
[0114] In certain embodiments, the second plurality of hydrophobic repeating units comprises repeating units derived from acrylate (e.g., alkyl acrylate, fluorinated acrylate or methacrylate), acrylamide (e.g., fluorinated acrylamide), styrene or hydrophobic amino acids. In certain embodiments, the second plurality of hydrophobic repeating units comprises repeating units derived from methacrylate. In certain embodiments, the second plurality of hydrophobic repeating units comprises repeating units derived from methacrylate 2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl ester, pentafluorophenyl methacrylate, styrene, methyl methacrylate, acrylonitrile, 2-chloroethyl methacrylate, 2-bromoethyl methacrylate and allyl methacrylate. In certain preferred embodiments, the second plurality of hydrophobic repeating units comprises repeating units derived from methacrylate 2,2-trifluoroethyl ester (TFEMA).
[0115] In certain embodiments, the plurality of cationic repeating units comprises repeating units derived from acrylate, acrylamide, styrene, or vinyl monomers substituted with amine, pyridinium, imidazolium, phosphonium, or pyrrolidinium. In certain embodiments, the plurality of cationic repeating units comprises repeating units derived from [2-(methacryloyloxy)ethyl]trimethylammonium chloride (MAETA), [3-(methacrylamido)propyl]trimethylammonium chloride, [2-(acryloyloxy)ethyl]trimethylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, 4-vinylbenzyl(triphenyl)phosphonium chloride, methacrylate(vinylbenzyl)trimethylammonium chloride, 3-vinylaniline, 4-vinylaniline, 2-isopropenylaniline, N-(3-aminopropyl)methacrylamide hydrochloride, N-vinylimidazolium salt, 1-allyl-3-vinylimidazolium salt, 1-allyl-2-methyl-5-vinyl-pyridinium salt, 1-allyl-5-vinyl-pyridinium salt, or 1-methyl-1-(1-vinylcyclohexyl)pyrrolidinium iodide. In certain preferred embodiments, the plurality of cationic repeating units comprises repeating units derived from 2-(methacryloyloxy)ethyl]trimethylammonium chloride.
[0116] In certain embodiments, the plurality of anionic repeating units comprises repeating units derived from acrylate, acrylamide, styrene or vinyl monomers substituted with carboxylic acid, sulfonic acid or phosphoric acid. In certain embodiments, the plurality of anionic repeating units comprises repeating units derived from methacrylate. In certain embodiments, the plurality of anionic repeating units comprises repeating units derived from methacrylic acid (MAA), 2-sulfoethyl methacrylate (SEMA), L-tryptophan-methacrylamide, D-tryptophan-methacrylamide, L or D-tryptophan-acrylamide, L or D-alanine-methacrylamide, L or D-alanine-acrylamide, L or D-valine-methacrylamide, L or D-valine-acrylamide, L or D-isoleucine-methacrylamide, L or D-isoleucine-acrylamide, L or D-alloisoleucine-methacrylamide, L or D-alloisoleucine-acrylamide, L or D-methionine-methacrylamide, L or D-methionine-acrylamide, L or D-phenylalanine-methacrylamide, L or D-phenylalanine-acrylamide, L or D-tyrosine-methacrylamide, L or D-tyrosine-acrylamide, L or D-histidine acid-methacrylamide, L or D-histidine-acrylamide, L or D-glutamic acid-methacrylamide, L or D-glutamic acid-methacrylamide, L or D-aspartic acid-acrylamide, L or D-aspartic acid-methacrylamide, acrylic acid, 2-carboxyethyl acrylate, mono-2-(methacryloyloxy)ethyl succinate, mono-2-(methacryloyloxy)ethyl maleate, sodium 4-vinylbenzenesulfonate, 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt, 2-acrylamido-2-methyl-1-propanesulfonic acid, 3-sulfopropyl acrylate potassium salt, 3-sulfopropyl methacrylate potassium salt, 3-vinylbenzoic acid, 4-vinylbenzoic acid, 2-vinylbenzoic acid, 4-(2-propenyl)benzoic acid, 2-methyl-2-propene-1-sulfonic acid sodium salt, vinylsulfonic acid sodium salt, vinylphosphonic acid or (4-vinylphenyl)methylphosphonic acid. In certain preferred embodiments, the plurality of anionic repeating units comprises repeating units derived from 2-sulfoethyl methacrylate. In other preferred embodiments, the plurality of anionic repeating units comprises repeating units derived from methacrylic acid.
[0117] In certain embodiments, the first copolymer is a block copolymer. In certain embodiments, the first copolymer is a statistical (e.g., approximately random) copolymer. In certain preferred embodiments, the first copolymer is a random copolymer. In certain embodiments, the second copolymer is a graft copolymer or a comb copolymer.
[0118] In certain embodiments, the second copolymer is a block copolymer. In certain embodiments, the first copolymer is a statistical (e.g., approximately random) copolymer. In certain preferred embodiments, the second copolymer is a random copolymer. In certain preferred embodiments, the second copolymer is a graft copolymer or a comb copolymer.
[0119] In certain embodiments, the effective pore size of the composite membrane is less than the effective pore size of a membrane made by coating only the first copolymer or only the second copolymer on the same porous support. In certain embodiments, the effective pore size is quantified by measuring the rejection rate of neutral (e.g., uncharged) solutes.
[0120] In certain embodiments, the first copolymer is cross-linked.
[0121] In certain embodiments, the second copolymer is cross-linked.
[0122] In another aspect, the disclosure provides a method for separating a solute from a solution, comprising contacting the solution with a composite membrane. In certain embodiments, the solution is passed through a composite membrane (e.g., filtered through a composite membrane). In certain embodiments, the solute is a salt (e.g., sodium chloride). In certain embodiments, the solution is seawater.
[0123] In another aspect, the present disclosure provides a method of making a composite membrane disclosed herein, comprising applying a first copolymer as disclosed herein and a second copolymer as disclosed herein to a porous support, thereby making a composite membrane disclosed herein.
[0124] In certain embodiments, the first copolymer and the second copolymer are sequentially applied to the porous support layer to form a double layer membrane. In certain embodiments, the first copolymer is first applied and then the second copolymer is applied. In certain embodiments, the second copolymer is first applied and then the first copolymer is applied. In other embodiments, the first copolymer and the second copolymer are applied to the porous support layer as a blend (e.g., the first copolymer and the second copolymer are mixed before applying) to form a blended membrane.
[0125] In certain embodiments, the first copolymer is dissolved in a protic solvent (e.g., methanol) prior to application. In certain embodiments, the second copolymer is dissolved in a protic solvent (e.g., methanol) prior to application. In certain embodiments, the first copolymer and the second copolymer are each dissolved in a protic solvent (e.g., methanol) prior to application.
[0126] definition
[0127] Unless otherwise defined herein, scientific and technical terms used in the present application shall have the meanings commonly understood by one of ordinary skill in the art.
[0128] The methods and techniques of the present disclosure are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.
[0129] Unless otherwise defined herein, chemical terms used herein are used according to conventional usage in the art as exemplified by “The McGraw-Hill Dictionary of Chemical Terms”, Parker S., Ed., McGraw-Hill, San Francisco, CA (1985).
[0130] All of the above and any other publications, patents, and published patent applications mentioned in this application are expressly incorporated herein by reference. In the event of a conflict, the present specification, including its specific definitions, will control.
[0131] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances where the event or circumstance occurs as well as instances where it does not occur. For example, "optionally substituted alkyl" means that the alkyl group may be substituted as well as instances where the alkyl group is not substituted.
[0132] It is understood that one of ordinary skill in the art can select substituents and substitution patterns on the compounds of the invention to produce chemically stable compounds that can be readily synthesized from readily available starting materials by techniques known in the art and those described below. If a substituent itself is substituted with more than one group, it is understood that these multiple groups can be on the same carbon or on different carbons, as long as a stable structure results.
[0133] As used herein, the term "optionally substituted" refers to the replacement of one to six hydrogen groups in a given structure with a specified substituent group, and the specific substituent groups include, but are not limited to: hydroxy, hydroxyalkyl, alkoxy, halogen, alkyl, nitro, silyl, acyl, acyloxy, aryl, cycloalkyl, heterocyclyl, amino, aminoalkyl, cyano, haloalkyl, haloalkoxy, -OCO-CH2-O-alkyl, -OP(O)(O-alkyl)2 or -CH2-OP(O)(O-alkyl)2. Preferably, "optionally substituted" refers to the replacement of one to four hydrogen groups in a given structure with the substituents mentioned above. More preferably, one to three hydrogen groups are replaced with substituents as mentioned above. It should be understood that the substituents can be further substituted.
[0134] As used herein, the term "alkyl" refers to a saturated aliphatic group, including but not limited to C1-C 10 Straight chain alkyl group or C1-C 10 Branched alkyl groups. Preferably, "alkyl" groups refer to C1-C6 straight chain alkyl groups or C1-C6 branched chain alkyl groups. More preferably, "alkyl" groups refer to C1-C4 straight chain alkyl groups or C1-C4 branched chain alkyl groups. Examples of "alkyl" include, but are not limited to, methyl, ethyl, 1-propyl, 2-propyl, n-butyl, sec-butyl, tert-butyl, 1-pentyl, 2-pentyl, 3-pentyl, neopentyl, 1-hexyl, 2-hexyl, 3-hexyl, 1-heptyl, 2-heptyl, 3-heptyl, 4-heptyl, 1-octyl, 2-octyl, 3-octyl or 4-octyl, etc. "alkyl" groups can be optionally substituted.
[0135] The term "acyl" is art-recognized and refers to a group represented by the general formula hydrocarbylC(O)-, preferably alkylC(O)-.
[0136] The term "acylamino" is art-recognized and refers to an amino group substituted with an acyl group and may be represented, for example, by the formula hydrocarbyl C(O)NH-.
[0137] The term "acyloxy" is art-recognized and refers to a group represented by the general formula hydrocarbylC(O)O-, preferably alkylC(O)O-.
[0138] The term "alkoxy" refers to an alkyl group having an oxygen attached thereto. Representative alkoxy groups include methoxy, ethoxy, propoxy, tert-butoxy, and the like.
[0139] The term "alkoxyalkyl" refers to an alkyl group substituted with an alkoxy group and can be represented by the general formula alkyl-O-alkyl.
[0140] The term "alkyl" refers to a saturated aliphatic group, including straight chain alkyl groups, branched chain alkyl groups, cycloalkyl (alicyclic) groups, alkyl substituted cycloalkyl groups and cycloalkyl substituted alkyl groups. In preferred embodiments, a straight chain or branched chain alkyl group has 30 or fewer carbon atoms in its backbone (e.g., C for a straight chain 1-30 , for the branched chain, C 3-30 ), more preferably 20 or less.
[0141] Furthermore, as used throughout the specification, examples and claims, the term "alkyl" is intended to include unsubstituted and substituted alkyl groups, the latter of which refers to alkyl moieties having substituents replacing hydrogen on one or more carbons of the hydrocarbon backbone, including haloalkyl groups such as trifluoromethyl and 2,2,2-trifluoroethyl and the like.
[0142] When used in conjunction with a chemical moiety such as acyl, acyloxy, alkyl, alkenyl, alkynyl, or alkoxy, the term "C x-y ” or “C x -C y " is intended to include groups containing from x to y carbons in the chain. C0 alkyl represents a hydrogen in a terminal position of the group, or internally, a bond. For example, C 1-6 Alkyl groups contain from one to six carbon atoms in the chain.
[0143] As used herein, the term "alkylamino" refers to an amino group substituted with at least one alkyl group.
[0144] As used herein, the term "alkylthio" refers to a thiol group substituted with an alkyl group and may be represented by the general formula alkylS-.
[0145] As used herein, the term "amido" refers to a group
[0146]
[0147] Where R 9 and R 10 Each independently represents hydrogen or a hydrocarbon group, or R 9 and R 10 Together with the N atom to which it is attached it forms a heterocyclic ring having 4 to 8 carbons in the ring structure.
[0148] The terms "amine" and "amino" are art-recognized and refer to unsubstituted and substituted amines and salts thereof, for example, a moiety represented by the formula
[0149]
[0150] Where R 9 , R 10 and R 10 ' each independently represents hydrogen or a hydrocarbon group, or R 9 and R 10 Together with the N atom to which it is attached it forms a heterocyclic ring having 4 to 8 carbons in the ring structure.
[0151] As used herein, the term "aminoalkyl" refers to an alkyl group substituted with an amino group.
[0152] As used herein, the term "aralkyl" refers to an alkyl group substituted with an aryl group.
[0153] As used herein, the term "aryl" includes substituted or unsubstituted monocyclic aromatic groups, wherein each atom of the ring is carbon. Preferably, the ring is a 5- to 7-membered ring, more preferably a 6-membered ring. The term "aryl" also includes a polycyclic ring system with two or more cyclic rings, wherein two or more carbons are shared by two adjacent rings, wherein at least one ring is aromatic, for example, other cyclic rings can be cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heteroaryl and / or heterocyclic radicals. Aryl groups include benzene, naphthalene, phenanthrene, phenol, aniline, etc.
[0154] The term "carbamate" is art-recognized and refers to a group of the formula,
[0155]
[0156] Where R 9 and R 10 independently represents hydrogen or a hydrocarbyl group.
[0157] As used herein, the term "carbocyclylalkyl" refers to an alkyl group substituted with a carbocyclyl group.
[0158] The term "carbocycle" includes 5-7 membered monocyclic rings and 8-12 membered bicyclic rings. Each ring of the bicyclic carbocycle can be selected from a saturated ring, an unsaturated ring, and an aromatic ring. Carbocycles include bicyclic molecules in which one, two, or three or more atoms are shared between the two rings. The term "fused carbocycle" refers to a bicyclic carbocycle in which each ring shares two adjacent atoms with another ring. Each ring of the fused carbocycle can be selected from a saturated ring, an unsaturated ring, and an aromatic ring. In an exemplary embodiment, an aromatic ring (e.g., phenyl) can be fused with a saturated or unsaturated ring (e.g., cyclohexane, cyclopentane, or cyclohexene). Any combination of saturated, unsaturated, and aromatic bicyclic rings is included in the definition of carbocycle, as long as the valence allows. Exemplary "carbocycles" include cyclopentane, cyclohexane, bicyclo [2.2.1] heptane, 1,5-cyclooctadiene, 1,2,3,4-tetrahydronaphthalene, bicyclo [4.2.0] oct-3-ene, naphthalene, and adamantane. Exemplary fused carbocycles include decahydronaphthalene, naphthalene, 1,2,3,4-tetrahydronaphthalene, bicyclo[4.2.0]octane, 4,5,6,7-tetrahydro-1H-indene, and bicyclo[4.1.0]hept-3-ene. "Carbocycle" may be substituted at any position or positions capable of bearing a hydrogen atom.
[0159] As used herein, the term "carbocyclylalkyl" refers to an alkyl group substituted with a carbocyclyl group.
[0160] The term "carbonate" is art-recognized and refers to the group -OCO2-.
[0161] As used herein, the term "carboxyl" refers to a group represented by the formula -CO2H.
[0162] The term "cycloalkyl" includes substituted or unsubstituted non-aromatic monocyclic structures, preferably 4- to 8-membered rings, more preferably 4- to 6-membered rings. The term "cycloalkyl" also includes polycyclic ring systems having two or more cyclic rings, wherein two or more carbon atoms are common to two adjacent rings, wherein at least one ring is a cycloalkyl group and the substituents (e.g., R 100 ) is connected to the cycloalkyl ring, for example, the other cyclic ring can be cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heteroaryl and / or heterocyclic. Heteroaryl groups include, for example, pyrrole, furan, thiophene, imidazole, oxazole, thiazole, pyrazole, pyridine, pyrazine, pyridazine, pyrimidine, benzodioxane, tetrahydroquinoline, etc.
[0163] As used herein, the term "ester" refers to the group -C(O)OR 9 , where R 9 represents a hydrocarbon group.
[0164] As used herein, the term "ether" refers to a hydrocarbyl group connected to another hydrocarbyl group through an oxygen. Thus, an ether substituent of a hydrocarbyl group may be hydrocarbyl-O-. An ether may be symmetrical or asymmetrical. Examples of ethers include, but are not limited to, heterocycle-O-heterocycle and aryl-O-heterocycle. Ethers include "alkoxyalkyl" groups, which may be represented by the general formula alkyl-O-alkyl.
[0165] As used herein, the terms "halo" and "halogen" mean halogen and include chlorine, fluorine, bromine and iodine.
[0166] As used herein, the terms "hetaralkyl" and "heteroaralkyl" refer to an alkyl group substituted with a heteroaryl group.
[0167] The terms "heteroaryl" and "hetaryl" include substituted or unsubstituted aromatic monocyclic structures, preferably 5- to 7-membered rings, more preferably 5- to 6-membered rings, whose ring structures contain at least one heteroatom, preferably one to four heteroatoms, more preferably one or two heteroatoms. The terms "heteroaryl" and "hetaryl" also include polycyclic ring systems having two or more cyclic rings, wherein two or more carbons are shared by two adjacent rings, wherein at least one ring is heteroaromatic, for example, the other cyclic rings can be cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heteroaryl and / or heterocyclyl. Heteroaryl groups include, for example, pyrrole, furan, thiophene, imidazole, oxazole, thiazole, pyrazole, pyridine, pyrazine, pyridazine and pyrimidine, etc.
[0168] As used herein, the term "heteroatom" means an atom of any element other than carbon or hydrogen. Preferred heteroatoms are nitrogen, oxygen and sulfur.
[0169] As used herein, the term "heterocyclylalkyl" refers to an alkyl group substituted with a heterocyclyl group.
[0170] The terms "heterocyclyl", "heterocycle" and "heterocyclic" refer to a substituted or unsubstituted non-aromatic ring structure, preferably a 3- to 10-membered ring, more preferably a 3- to 7-membered ring, whose ring structure contains at least one heteroatom, preferably one to four heteroatoms, more preferably one or two heteroatoms. The terms "heterocyclyl" and "heterocyclic" also include polycyclic ring systems having two or more cyclic rings, wherein two or more carbon atoms are common to two adjacent rings, wherein at least one ring is heterocyclic, for example, the other cyclic rings can be cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heteroaryl and / or heterocyclyl. Heterocyclyl groups include, for example, piperidine, piperazine, pyrrolidine, morpholine, lactone, lactam, etc.
[0171] As used herein, the term "hydrocarbyl" refers to a group bonded through a carbon atom that does not have a =O or =S substituent, and typically has at least one carbon-hydrogen bond and a backbone that is primarily carbon, but may optionally contain heteroatoms. Thus, for the purposes of this application, groups such as methyl, ethoxyethyl, 2-pyridyl, and even trifluoromethyl are considered hydrocarbyl, but substituents such as acetyl (which has a =O substituent on the attached carbon) and ethoxy (which is attached through oxygen rather than carbon) are not. Hydrocarbyl groups include, but are not limited to, aryl, heteroaryl, carbocyclic, heterocyclic, alkyl, alkenyl, alkynyl, and combinations thereof.
[0172] As used herein, the term "hydroxyalkyl" refers to an alkyl group substituted with a hydroxy group.
[0173] When used in conjunction with chemical moieties such as acyl, acyloxy, alkyl, alkenyl, alkynyl or alkoxy, the term "lower" is intended to include groups wherein the number of atoms in the substituent is ten or less, preferably six or less. For example, "lower alkyl" refers to an alkyl group containing ten or less carbon atoms, preferably six or less carbon atoms. In certain embodiments, the acyl, acyloxy, alkyl, alkenyl, alkynyl or alkoxy substituents defined herein are respectively lower acyl, lower acyloxy, lower alkyl, lower alkenyl, lower alkynyl or lower alkoxy, whether they occur alone or in combination with other substituents, such as in the description of hydroxyalkyl and aralkyl (in this case, for example, when calculating the carbon atoms in the alkyl substituent, the atoms in the aryl group are not counted).
[0174] The terms "polycyclyl", "polycycle" and "polycyclic" refer to two or more rings (e.g., cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heteroaryl and / or heterocyclyl) in which two or more atoms are common to two adjacent rings, for example, these rings are "fused rings". Each of the polycyclic rings can be substituted or unsubstituted. In certain embodiments, each ring of the polycyclic contains 3 to 10 atoms in the ring, preferably 5 to 7 atoms.
[0175] The term "sulfate" is art-recognized and refers to the group -OSO3H or a pharmaceutically acceptable salt thereof.
[0176] The term "sulfonylamino" is art-recognized and refers to a group represented by the general formula
[0177]
[0178] Where R 9 and R 10 independently represent hydrogen or a hydrocarbon group.
[0179] The term "sulfoxide" is art-recognized and refers to the group -S(O)-.
[0180] The term "sulfonate" is art-recognized and refers to the group SO3H or a pharmaceutically acceptable salt thereof.
[0181] The term "sulfone" is art-recognized and refers to the group -S(O)2-.
[0182] The term "substituted" refers to a moiety with a substituent that replaces hydrogen on one or more carbons of the main chain. It should be understood that "replacement" or "replaced by..." includes implicit conditions, i.e., such substitution is consistent with the allowed valence of the substituted atom and the substituent, and the substitution produces a stable compound, for example, a compound that does not spontaneously undergo transformation, such as by rearrangement, cyclization, elimination, etc. As used herein, the term "substituted" is intended to include all allowed substituents of organic compounds. In a broad sense, allowed substituents include acyclic and cyclic, branched and unbranched, carbocyclic and heterocyclic, aromatic and non-aromatic substituents of organic compounds. For appropriate organic compounds, allowed substituents may be one or more and the same or different. For purposes of the present invention, heteroatoms such as nitrogen may have hydrogen substituents and / or any allowed substituents of organic compounds described herein that satisfy the valence of heteroatoms. Substituents may include any of the substituents described herein, for example, halogen, hydroxy, carbonyl (e.g., carboxyl, alkoxycarbonyl, formyl or acyl), thiocarbonyl (e.g., thioester, thioacetate or thioformate), alkoxy, phosphoryl, phosphate, phosphonate, phosphinate, amino, amido, amidino, imino, cyano, nitro, azido, sulfhydryl, alkylthio, sulfate, sulfonate, sulfamoyl, sulfonamido, sulfonyl, heterocyclyl, aralkyl or aromatic or heteroaromatic moieties. It will be appreciated by those skilled in the art that the moieties substituted on the hydrocarbon chain may themselves be substituted if appropriate.
[0183] As used herein, the term "sulfanyl" refers to an alkyl group substituted with a thiol group.
[0184] As used herein, the term "thioester" refers to the group -C(O)SR 9 or -SC(O)R 9
[0185] Where R 9 It represents a hydrocarbon group.
[0186] As used herein, the term "thioether" corresponds to an ether in which oxygen is replaced by sulfur.
[0187] The term "urea" is art-recognized and can be represented by the general formula
[0188]
[0189] Where R 9 and R 10 independently represent hydrogen or a hydrocarbon group.
[0190] Many compounds useful in the methods and compositions of the present disclosure have at least one stereocenter in their structure. The stereocenter can exist in the R or S configuration, and the R and S symbols correspond to the rules described in Pure Appl. Chem. (1976), 45, 11-30. The present disclosure encompasses all stereoisomeric forms of compounds, salts, prodrugs, or mixtures thereof, such as enantiomeric and diastereomeric forms (including all possible stereoisomer mixtures). See, for example, WO 01 / 062726.
[0191] Furthermore, certain compounds containing alkenyl groups may exist as Z (zusammen) or E (entgegen) isomers. In each case, the present disclosure includes both the mixture and the individual isomers.
[0192] As used herein, the term "operating conditions" refers to the conditions under which a filter membrane is typically used or operated. For example, in certain embodiments, the filter membrane may be designed to treat produced water (e.g., water produced as a byproduct during oil and gas extraction), gray water (e.g., water that has been used in homes, commerce, and industry), hot streams (e.g., fracking water), brine streams, water from mine drainage, or industrial clean water. In certain embodiments, the term "operating conditions" may refer to conditions associated with the treatment of acidic water (optionally containing suspended solids (e.g., inorganic salts). In other embodiments, operating conditions may refer to conditions associated with the treatment of alkaline water (optionally containing suspended solids (e.g., inorganic salts).
[0193] Example
[0194] Having now generally described the invention, the invention will be more readily understood by reference to the following examples, which are included solely for the purpose of illustrating certain aspects and embodiments of the invention and are not intended to limit the invention.
[0195] Example 1
[0196] Synthesis and membrane preparation of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) as amphiphilic polyelectrolyte complex (APEC) multilayers
[0197] Synthesis of A+(P(TFEMA-r-MAETA)). MAETA (4.00 g, 19.3 mmol) and TFEMA (4.00 g, 23.8 mmol) were dissolved in DMSO (32 mL) in this order. AIBN (0.008 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 60°C while stirring at 300 rpm for 17 hours. The flask was removed from the oil bath and the seal was opened, and 0.8 g of MEHQ was added to terminate the reaction. The reaction mixture was then precipitated in acetone and purified by stirring two fresh portions of ethanol and hexane in a 1:3 volume ratio for at least 3 hours. Finally, the copolymer was dried in a vacuum oven at 60°C for 72 hours. The composition of the copolymer was determined according to 1 H-NMR spectrum ( Figure 1 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 41 mol% MAETA and 59 mol% TFEMA. The final conversion of the reaction was 45%.
[0198] Synthesis of S-(P(TFEMA-r-SEMA)). SEMA (4.00 g, 20.6 mmol) and TFEMA (4.00 g, 23.8 mmol) were dissolved in DMSO (32 mL) in this order. AIBN (0.008 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 60°C while stirring at 300 rpm for 17 hours. The flask was removed from the oil bath and the seal was opened, and 0.8 g of MEHQ was added to terminate the reaction. The reaction mixture was then precipitated in a 1:3 volume ratio of ethanol and hexane and purified by stirring two fresh 2:3 volume ratios of ethanol and hexane for at least 3 hours. Finally, the copolymer was dried in a vacuum oven at 60°C for 72 hours. The composition of the copolymer was based on 1 H-NMR spectrum ( Figure 2 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 37 mol% SEMA and 63 mol% TFEMA. The final conversion of the reaction was 55%.
[0199] After the synthesis of both, copolymer A+ and S- are used to prepare thin film composite membranes. At about 25°C, each copolymer (0.5g) is dissolved in methanol (9.5g) respectively. Both copolymer solutions are passed through a 0.45 micron syringe filter (Whatman) and degassed in a vacuum oven for at least 1 hour. Films are prepared by applying each copolymer solution of a thin layer once on a commercially available ultrafiltration (UF) membrane using a film coating rod, and in addition, a 10-minute solvent evaporation period is used between coatings. When S- is first coated, the film is named SA, and when A+ is first coated, the film is named AS. PS35 (PSf) ultrafiltration membrane purchased from Solecta (Oceanside, Calif.) is used as a base membrane. After coating, the film is immersed in a water bath.
[0200] In addition, coatings containing lower concentrations of top layer solutions were tested. SA and AS represent both solutions at 5 wt %, as described above. SA1 and AS1 represent the first casting solution at 5 wt % and the second at 1 wt %. SA0.2 and AS0.2 represent the first casting solution at 5 wt % and the second at 0.2 wt %. Films with only one layer, S- and A+, were also prepared as controls.
[0201] The thickness and morphology of the film were determined by examining freeze fracture cross sections of the film using scanning electron microscopy. It was observed that the coating thickness was approximately 0.6 microns. Figure 3 .
[0202] Example 2
[0203] Water permeability and water absorption of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) used as amphiphilic polyelectrolyte complex (APEC) multilayers
[0204] In this example, a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 The pure water flux through the membrane described in Example 1 was measured using an Amicon 8010 stirred dead-end filtration cell (Millipore). The cell was stirred at 500 rpm and tested at 40 psi. After a stabilization period of at least one hour, permeate samples were collected over 120 minutes and weighed. The values obtained were divided by the filtration area and the experimental time to obtain flux. The flux values were normalized by pressure to obtain pure water permeability (Tables 1, 2, and 3). These membranes have permeabilities comparable to commercially available membranes for nanofiltration and ultrafiltration.
[0205] Table 1. Water permeability of the control and two APEC multilayers SA and SA.
[0206]
[0207] Table 2. Water permeability of control and all layers with S- as first layer.
[0208]
[0209] Table 3. Water permeability of control and all layers with A+ as first layer.
[0210]
[0211] Water absorption measurements were performed using polymer films approximately 40 microns thick (Table 4). The films were prepared by mixing equal amounts (by weight) of S- and A+ copolymer solutions (5 wt % each) on a Teflon disk and leaving the mixture overnight on a nutating mixer to dry. The films were equilibrated in deionized water at room temperature overnight, excess water was removed by placing the film on a Kimwipe for 5 seconds, and the sample was weighed thereafter. The same sample was dried overnight in a vacuum oven set at 60°C to obtain the dry weight.
[0212] Table 4. Water absorption of control and APEC
[0213] S- S A+ Water absorption (%) 285±15 69±8 1450±310
[0214] Example 3
[0215] Neutral Solute Rejection of Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-(Methacryloyloxy)ethyl]trimethylammonium Chloride) (A+) and Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-Sulfonethyl Methacrylate) (S-) as Amphiphilic Polyelectrolyte Complex (APEC) Multilayers
[0216] In this example, membranes prepared as described in Example 1 were used in experiments designed to determine their effective pore size or size cutoff. Dye molecules and sugars were used to probe this property. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2. The pool was stirred at 500 rpm and tested at 40 psi. The pool was stirred at 500 rpm to minimize the concentration polarization effect. After allowing pure water to flow through the membrane for at least one hour, the pool was emptied and a 0.1 mM solution of the probe dye (vitamin B12 (B12) or riboflavin (Rib)) in water or a 4000 ppm solution of sugar molecules (sucrose or glucose) or glycerol in water was placed in the pool. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected to analyze and calculate the solute rejection rate (%) by a COD kit (K-7365, CHEMetrics) or a UV-vis spectrophotometer (Genesys10, ThermoScientific) ( Figure 4 and 5 ). Rinse the cell several times with water. Filter the pure water through the membrane until the permeate is completely clear, then switch to the new solute.
[0217] Example 4
[0218] Salt rejection of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) used as amphiphilic polyelectrolyte complex (APEC) multilayers
[0219] In this example, membranes prepared as described in Example 1 were used in experiments to determine their salt rejection properties. This property was probed using different salts at different concentrations, which can be easily measured by a standard conductivity probe. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a solution of the probe salt in water was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by the conductivity probe and the salt rejection (%) was calculated ( Figure 6-14 ). Rinse the cell several times with water. Filter pure water through the membrane until the permeate volume reaches 1 mL, then switch to new salt solution.
[0220] Example 5
[0221] Antifouling properties of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) used as amphiphilic polyelectrolyte complex (APEC) multilayers
[0222] In this example, two membranes, S- and SA, prepared as described in Example 1, were used in experiments to determine their antifouling properties. The experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 The cell was stirred at 500 rpm. The feed solution consisted of 1500 ppm of an oil-in-water emulsion (9:1 ratio of soybean oil:DC 193 surfactant from Dow-Corning) prepared by blending the oil, water and surfactant using a blender at high rpm for 3 minutes.
[0223] Example 6
[0224] Synthesis and membrane preparation of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(methacrylic acid) (M-) as amphiphilic polyelectrolyte complex (APEC) multilayers
[0225] The same protocol as in Example 1 was used to synthesize A+ and the same copolymer ( Figure 1 ).
[0226] Synthesis of M-(P(TFEMA-r-MAA)). MAA (10.00 g) and TFEMA (10.00 g) were dissolved in DMSO (100 mL) in this order. AIBN (0.02 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 55°C while stirring at 300 rpm for 4 hours. The flask was removed from the oil bath and the seal was opened, and 2 g of MEHQ in 10 mL of DMSO was added to terminate the reaction. The reaction mixture was then precipitated in a 1:3 volume ratio of ethanol and hexane and purified by stirring two fresh 1:3 volume ratios of ethanol and hexane for at least 8 hours. Finally, the copolymer was dried in a vacuum oven at 50°C for 120 hours. The composition of the copolymer was determined according to 1 H-NMR spectrum ( Fig.16 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 59 mol% MAA and 41 mol% TFEMA. The final conversion of the reaction was 35%.
[0227] After the synthesis of both, copolymer A+ and M- are used to prepare thin film composite membranes. At about 25°C, each copolymer (0.5g) is dissolved in methanol (9.5g) respectively. Both copolymer solutions are passed through a 0.45 micron syringe filter (Whatman) and degassed in a vacuum oven for at least 1 hour. Films are prepared by applying each copolymer solution of a thin layer once on a commercially available ultrafiltration (UF) membrane using a film coating rod, and in addition, a 10-minute solvent evaporation period is adopted between coatings. When M- is first coated, the film is named MA, and when A+ is first coated, the film is named AM. PS35 (PSf) ultrafiltration membrane purchased from Solecta (Oceanside, Calif.) is used as a base membrane. After coating, the film is immersed in a water bath.
[0228] The thickness and morphology of the films were determined by examining freeze fracture cross sections of the films using scanning electron microscopy. It was observed that the coating thickness was approximately 0.4 microns. Fig.17 .
[0229] Example 7
[0230] Water permeability of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(methacrylic acid) (M-) used as amphiphilic polyelectrolyte complex (APEC) multilayers
[0231] In this example, a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 The pure water flux through the membrane AM described in Example 6 was measured using an Amicon 8010 stirred dead-end filtration cell (Millipore). The cell was stirred at 500 rpm and the test was performed at 40 psi. After a stabilization period of at least one hour, permeate samples were collected over 120 minutes and weighed. The values obtained were divided by the filtration area and the experimental time to obtain the flux. The flux values were normalized to pressure to obtain 1.5 L / m 2 .h.bar pure water permeability.
[0232] Example 8
[0233] Neutral Solute Rejection of Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-(Methacryloyloxy)ethyl]trimethylammonium Chloride) (A+) and Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(Methacrylic Acid) (M-) as Amphiphilic Polyelectrolyte Complex (APEC) Multilayers
[0234] In this example, membranes prepared as described in Example 6 were used in experiments designed to determine their effective pore size or size cutoff. Vitamin B12 was used to probe this property. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a 0.1 mM solution of the probe dye (vitamin B12 (B12)) in water was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by UV-vis spectrophotometer (Genesys10, ThermoScientific) and the solute rejection was calculated to be 95.3%.
[0235] Example 9
[0236] Synthesis and membrane preparation of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(methacrylic acid) (M-) as amphiphilic polyelectrolyte complex (APEC) blends
[0237] A+ and M- were synthesized using the same protocol as in Examples 1 and 6, and using the same copolymers (respectively, Figure 1 and 16 ).
[0238] After the synthesis of both, copolymer A+ and M- are used to prepare thin film composite membrane.At about 25 ℃, each copolymer (0.5g) is dissolved in methanol (9.5g) respectively.With different ionizable / charged monomer unit molar ratios, two solutions are combined into solution and all solutions are passed through 0.45 micron syringe filter (Whatman) and degassed in vacuum oven for at least 1 hour.By using film coating rod, a thin layer of combined solution is coated on commercial ultrafiltration (UF) membrane to prepare membrane.PS35 (PSf) ultrafiltration membrane purchased from Solecta (Oceanside, Calif.) is used as base membrane.After coating, membrane is immersed in a water bath.
[0239] The thickness and morphology of the films were determined by examining freeze fracture cross sections of the films using scanning electron microscopy. It was observed that the coating thickness was approximately 3 microns. Fig.18 .
[0240] Example 10
[0241] Water permeability of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(methacrylic acid) (M-) as amphiphilic polyelectrolyte complex (APEC) blends
[0242] In this example, the volume of the cell used was 10 mL and the effective filtration area was 4.1 cm 2 The pure water flux through the membrane described in Example 9 was measured using an Amicon 8010 stirred dead-end filtration cell (Millipore). The cell was stirred at 500 rpm and tested at 40 psi. After a stabilization period of at least one hour, permeate samples were collected over 120 minutes and weighed. The values obtained were divided by the filtration area and the experimental time to obtain the flux. The flux values were normalized by pressure to obtain the pure water permeability ( Fig.19 ). These membranes have permeabilities comparable to commercially available membranes for nanofiltration and ultrafiltration.
[0243] Embodiment 11
[0244] Neutral Solute Rejection of Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-(Methacryloyloxy)ethyl]trimethylammonium Chloride) (A+) and Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(Methacrylic Acid) (M-) as Amphiphilic Polyelectrolyte Complex (APEC) Blends
[0245] In this example, membranes prepared as described in Example 9 were used in experiments designed to determine their effective pore size or size cutoff. Vitamin B12 was used to probe this property. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a 0.1 mM solution of the probe dye (vitamin B12 (B12)) in water was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by UV-vis spectrophotometer (Genesys10, ThermoScientific) and the solute rejection rate ( Fig. 20 ).
[0246] Example 12
[0247] Salt rejection of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(methacrylic acid) (M-) as amphiphilic polyelectrolyte complex (APEC) blends
[0248] In this example, membranes prepared as described in Example 9 were used in experiments to determine their salt rejection properties. This property was probed using different salts at different concentrations, which can be easily measured by a standard conductivity probe. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a solution of the probe salt in water was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by the conductivity probe and the salt rejection (%) was calculated ( Figure 21-23 ). Rinse the cell several times with water. Filter pure water through the membrane until the permeate volume reaches 1 mL, then switch to new salt solution.
[0249] Embodiment 13
[0250] Synthesis and membrane preparation of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A2+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) as amphiphilic polyelectrolyte complex (APEC) multilayers
[0251] In this example, poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A2+) was synthesized using a higher TFEMA content. The anionic copolymer was the same S-copolymer described in Example 1.
[0252] Synthesis of A2+(P(TFEMA-r-MAETA)). MAETA (3.50 g) and TFEMA (6.50 g) were dissolved in DMSO (40 mL) in this order. AIBN (0.01 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 60°C while stirring at 300 rpm for 17 hours. The flask was removed from the oil bath and the seal was opened, and 1.0 g of MEHQ was added to terminate the reaction. The reaction mixture was then precipitated in acetone and purified by stirring two portions of fresh acetone for at least 3 hours and then two portions of fresh DI water for at least 3 hours. Finally, the copolymer was dried in a vacuum oven at 60°C for 72 hours. The composition of the copolymer was based on 1 H-NMR spectrum ( Fig.24 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 34 mol% MAETA and 66 mol% TFEMA. The final conversion of the reaction was 35%.
[0253] Synthesis of S-(P(TFEMA-r-SEMA)). SEMA (4.00 g, 20.6 mmol) and TFEMA (4.00 g, 23.8 mmol) were dissolved in DMSO (32 mL) in this order. AIBN (0.008 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 60°C while stirring at 300 rpm for 17 hours. The flask was removed from the oil bath and the seal was opened, and 0.8 g of MEHQ was added to terminate the reaction. The reaction mixture was then precipitated in a 1:3 volume ratio of ethanol and hexane and purified by stirring two fresh 2:3 volume ratios of ethanol and hexane for at least 3 hours. Finally, the copolymer was dried in a vacuum oven at 60°C for 72 hours. The composition of the copolymer was determined according to 1 H-NMR spectrum ( Fig.25 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 37 mol% SEMA and 63 mol% TFEMA. The final conversion of the reaction was 55%.
[0254] After the synthesis of both, copolymer A2+ and S- are used to prepare thin film composite membranes. At about 25°C, each copolymer (0.5g) is dissolved in methanol (9.5g) respectively. Both copolymer solutions are passed through a 0.45 micron syringe filter (Whatman) and degassed in a vacuum oven for at least 1 hour. Films are prepared by applying each copolymer solution of a thin layer once on a commercially available ultrafiltration (UF) membrane using a film coating rod, and in addition, a 10-minute solvent evaporation period is used between coatings. When S- is first coated, the film is named SA2, and when A2+ is first coated, the film is named A2S. PS35 (PSf) ultrafiltration membrane purchased from Solecta (Oceanside, Calif.) is used as a base membrane. After coating, the film is immersed in a water bath.
[0255] The thickness and morphology of the films were determined by examining freeze fracture cross sections of the films using scanning electron microscopy. It was observed that the coating thickness was approximately 0.5 microns. Fig.26 .
[0256] Embodiment 14
[0257] Water permeability of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A2+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) as amphiphilic polyelectrolyte complex (APEC) multilayers
[0258] In this example, the volume of the cell used was 10 mL and the effective filtration area was 4.1 cm 2 The pure water flux through the membrane described in Example 13 was measured using an Amicon 8010 stirred dead-end filtration cell (Millipore). The cell was stirred at 500 rpm and tested at 40 psi. After a stabilization period of at least one hour, permeate samples were collected over 120 minutes and weighed. The values obtained were divided by the filtration area and the experimental time to obtain the flux. The flux values were normalized by pressure to obtain the pure water permeability. The permeability of A2S was 8.5 ± 0.9 L / m 2 .h.bar. The permeability of A2+ (only A2+ coating) is 59±11L / m 2 These membranes have permeabilities comparable to commercially available membranes for nanofiltration and ultrafiltration.
[0259] Embodiment 15
[0260] Neutral Solute Rejection of Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-(Methacryloyloxy)ethyl]trimethylammonium Chloride) (A2+) and Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-Sulfonethyl Methacrylate) (S-) as Amphiphilic Polyelectrolyte Complex (APEC) Multilayers
[0261] In this example, membranes prepared as described in Example 13 were used in experiments designed to determine their effective pore size or size cutoff. Dye molecules and sugars were used to probe this property. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The pool was stirred at 500 rpm and tested at 40 psi. The pool was stirred at 500 rpm to minimize the concentration polarization effect. After allowing pure water to flow through the membrane for at least one hour, the pool was emptied and a 0.1 mM solution of the probe dye (vitamin B12 (B12) or riboflavin (Rib)) in water or a 4000 ppm solution of sugar molecules (sucrose or glucose) or glycerol in water was placed in the pool. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected to analyze and calculate the solute rejection rate (%) by a COD kit (K-7365, CHEMetrics) or a UV-vis spectrophotometer (Genesys10, ThermoScientific) ( Figure 27-28 ). Rinse the cell several times with water. Filter the pure water through the membrane until the permeate is completely clear, then switch to the new solute.
[0262] Example 16
[0263] Salt rejection of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A2+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S-) as amphiphilic polyelectrolyte complex (APEC) multilayers
[0264] In this example, membranes prepared as described in Example 13 were used in experiments to determine their salt rejection properties. This property was probed using different salts at different concentrations, which can be easily measured by a standard conductivity probe. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2. The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a solution of the probe salt in water was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by the conductivity probe and the salt rejection (%) was calculated ( Figure 29-31 ). Rinse the cell several times with water. Filter pure water through the membrane until the permeate volume reaches 1 mL, then switch to new salt solution.
[0265] Embodiment 17
[0266] Synthesis and membrane preparation of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S2-) as amphiphilic polyelectrolyte complex (APEC) multilayers
[0267] In this example, poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S2-) was synthesized using a higher TFEMA content, and the cationic copolymer was the same A+ copolymer described in Example 1.
[0268] Synthesis of A+(P(TFEMA-r-MAETA)). MAETA (4.00 g, 19.3 mmol) and TFEMA (4.00 g, 23.8 mmol) were dissolved in DMSO (32 mL) in this order. AIBN (0.008 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 60°C while stirring at 300 rpm for 17 hours. The flask was removed from the oil bath and the seal was opened, and 0.8 g of MEHQ was added to terminate the reaction. The reaction mixture was then precipitated in acetone and purified by stirring two fresh portions of ethanol and hexane in a 1:3 volume ratio for at least 3 hours. Finally, the copolymer was dried in a vacuum oven at 60°C for 72 hours. The composition of the copolymer was determined according to 1 H-NMR spectrum ( Fig.32 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 41 mol% MAETA and 59 mol% TFEMA. The final conversion of the reaction was 45%.
[0269] Synthesis of S2-(P(TFEMA-r-SEMA)). SEMA (1.75 g) and TFEMA (3.25 g) were dissolved in DMSO (20 mL) in this order. AIBN (0.005 g) was added to the flask. The flask was sealed and nitrogen was bubbled through the reaction mixture for 30 minutes to remove any dissolved oxygen. The flask was then placed in an oil bath set at 60°C while stirring at 300 rpm for 17 hours. The flask was removed from the oil bath and the seal was opened, and 0.5 g of MEHQ was added to terminate the reaction. The reaction mixture was then precipitated in DI water and purified by stirring two portions of fresh DI water for at least 3 hours. The copolymer was dried in a vacuum oven at 60°C for 48 hours. Thereafter, the copolymer was purified by stirring two portions of fresh hexane for at least 3 hours. Finally, the copolymer was dried in a vacuum oven at 60°C for 72 hours. The composition of the copolymer was determined according to 1 H-NMR spectrum ( Fig.33 ) was calculated using the ratio of protons from the two different monomer units. The calculated composition was: 30 mol% SEMA and 70 mol% TFEMA. The final conversion of the reaction was 21%.
[0270] After the synthesis of both, copolymer A+ and S2-are used to prepare thin film composite membranes. At about 25°C, each copolymer (0.5g) is dissolved in methanol (9.5g) respectively. Two copolymer solutions are degassed in a vacuum oven for at least 1 hour. Films are prepared by coating each copolymer solution of a thin layer once on a commercially available ultrafiltration (UF) membrane using a membrane coating rod, and in addition, a 10-minute solvent evaporation period is used between coatings. When S2-is coated first, the film is named S2A, and when A+ is coated first, the film is named AS2. PS35 (PSf) ultrafiltration membrane purchased from Solecta (Oceanside, Calif.) is used as a base membrane. After coating, the film is immersed in a water bath.
[0271] The thickness and morphology of the films were determined by examining freeze fracture cross sections of the films using scanning electron microscopy. It was observed that the coating thickness was approximately 0.4 microns. Fig.34 .
[0272] Embodiment 18
[0273] Water permeability of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S2-) used as amphiphilic polyelectrolyte complex (APEC) multilayers
[0274] In this example, the volume of the cell used was 10 mL and the effective filtration area was 4.1 cm2 The pure water flux through the membrane described in Example 17 was measured using an Amicon 8010 stirred dead-end filtration cell (Millipore). The cell was stirred at 500 rpm and tested at 40 psi. After a stabilization period of at least one hour, permeate samples were collected over 120 minutes and weighed. The values obtained were divided by the filtration area and the experimental time to obtain the flux. The flux values were normalized by pressure to obtain the pure water permeability. The permeability of AS2 was 4.7 ± 0.8 L / m 2 .h.bar. The permeability of S2- (only S2-coated) is 98±17L / m 2 These membranes have permeabilities comparable to commercially available membranes for nanofiltration and ultrafiltration.
[0275] Embodiment 19
[0276] Neutral Solute Rejection of Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-(Methacryloyloxy)ethyl]trimethylammonium Chloride) (A+) and Poly(2,2,2-Trifluoroethyl Methacrylate)-Random-Poly(2-Sulfonethyl Methacrylate) (S2-) as Amphiphilic Polyelectrolyte Complex (APEC) Multilayers
[0277] In this example, membranes prepared as described in Example 17 were used in experiments designed to determine their effective pore size or size cutoff. Dye molecules were used to probe this property. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a 0.1 mM aqueous solution of the probe dye (vitamin B12 (B12) or riboflavin (Rib)) was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by UV-vis spectrophotometer (Genesys10, ThermoScientific) and the solute rejection rate (%) was calculated ( Fig.35 ). Rinse the cell several times with water. Filter the pure water through the membrane until the permeate is completely clear, then switch to the new solute.
[0278] Embodiment 20
[0279] Salt rejection of poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-(methacryloyloxy)ethyl]trimethylammonium chloride) (A+) and poly(2,2,2-trifluoroethyl methacrylate)-random-poly(2-sulfoethyl methacrylate) (S2-) used as amphiphilic polyelectrolyte complex (APEC) multilayers
[0280] In this example, membranes prepared as described in Example 17 were used in experiments to determine their salt rejection properties. This property was probed using different salts at different concentrations, which can be easily measured by a standard conductivity probe. Retention experiments were performed on an Amicon 8010 stirred dead-end filtration cell (Millipore) with a cell volume of 10 mL and an effective filtration area of 4.1 cm 2 . The cell was stirred at 500 rpm and tested at 40 psi. The cell was stirred at 500 rpm to minimize concentration polarization effects. After allowing pure water to flow through the membrane for at least one hour, the cell was emptied and a solution of the probe salt in water was placed in the cell. After rejecting the first 1 mL, in order to avoid pure water contamination, sufficient volume was collected for analysis by the conductivity probe and the salt rejection (%) was calculated ( Figure 36-38 ). Rinse the cell several times with water. Filter pure water through the membrane until the permeate volume reaches 1 mL, then switch to new salt solution.
[0281] Incorporated by Reference
[0282] All publications and patents mentioned herein are hereby incorporated by reference in their entirety to the same extent as if each individual publication or patent was specifically and individually indicated to be incorporated by reference. In the event of a conflict, the present application, including any definitions herein, will control.
[0283] Equivalent
[0284] Although specific embodiments of the present invention have been discussed, the above description is illustrative and not restrictive. After reading this specification and the appended claims, many variations of the present invention will become apparent to those skilled in the art. The full scope of the present invention should be determined by reference to the full scope of the claims and their equivalents, the description, and such variations.
Claims
1. A composite membrane comprising a porous support; and a selective layer comprising a first copolymer and a second copolymer; wherein: The first copolymer comprises a first plurality of hydrophobic repeating units and a plurality of cationic repeating units; The second copolymer comprises a second plurality of hydrophobic repeating units and a plurality of anionic repeating units; and The first copolymer and the second copolymer are substantially insoluble in water (eg, under operating conditions).
2. The composite membrane of claim 1, wherein the first copolymer and the second copolymer are insoluble in water (eg, under operating conditions). The composite membrane according to claim 1 , wherein the composite membrane is a thin film composite membrane. 4 . The composite film of claim 1 , wherein the composite film has a thickness of about 20 μm to about 1,000 μm. 5 . The composite film of claim 1 , wherein the composite film has a thickness of about 50 μm to about 200 μm.
6. The composite membrane of any one of claims 1-5, wherein the selective layer has a thickness of about 30 nm to about 5 μm.
7. The composite membrane of any one of claims 1-6, wherein the selective layer has a thickness of about 30 nm to about 1,000 nm.
8. A composite membrane according to any one of claims 1-7, wherein the selective layer has a thickness of about 10 nm, about 25 nm, about 50 nm, about 75 nm, about 100 nm, about 125 nm, about 150 nm, about 175 nm, about 200 nm, about 225 nm, about 250 nm, about 275 nm, about 300 nm, about 325 nm, about 350 nm, about 375 nm, about 400 nm, about 425 nm, about 450 nm, about 475 nm, about 500 nm, about 525 nm, about 550 nm, about 575 nm, or about 600 nm.
9. The composite membrane of any one of claims 1-8, wherein the selective layer has a thickness of about 400 nm, about 425 nm, about 450 nm, about 475 nm, about 500 nm, about 525 nm, about 550 nm, about 575 nm, or about 600 nm.
10. The composite membrane of any one of claims 1 to 9, wherein the plurality of cationic repeating units are partially positively charged in water (eg, in water at neutral pH or in water under operating conditions).
11. The composite membrane of any one of claims 1-9, wherein the plurality of cationic repeating units are positively charged in water (eg, in water at neutral pH or in water under operating conditions).
12. The composite membrane of any one of claims 1-11, wherein the plurality of anionic repeating units are partially negatively charged in water (eg, in water at neutral pH or in water under operating conditions).
13. The composite membrane of any one of claims 1-11, wherein the plurality of anionic repeating units are negatively charged in water (eg, in water at neutral pH or in water under operating conditions).
14. The composite membrane of any one of claims 1-13, wherein the selective layer consists essentially of the first copolymer and the second copolymer.
15. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 5-80 wt% of the plurality of cationic repeating units.
16. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 15-75 wt% of the plurality of cationic repeating units.
17. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 20-50 wt% of the plurality of cationic repeating units.
18. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 10 wt%, about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, about 60 wt%, about 70 wt%, or about 80 wt% of the plurality of cationic repeating units.
19. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 5-80 mol% of the plurality of cationic repeating units.
20. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 15-75 mol% of the plurality of cationic repeating units.
21. The composite membrane of any one of claims 1-14, wherein the first copolymer comprises about 20-50 mol% of the plurality of cationic repeating units.
22. The composite membrane of any one of claims 1-21, wherein the first copolymer comprises about 10 mol%, about 20 mol%, about 30 mol%, about 40 mol%, about 50 mol%, about 60 mol%, about 70 mol%, or about 80 mol% of the plurality of cationic repeating units.
23. The composite membrane of any one of claims 1-21, wherein the first copolymer comprises about 10 wt%, about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, about 60 wt%, about 70 wt%, or about 80 wt% of the first plurality of hydrophobic repeating units.
24. The composite membrane of any one of claims 1-21, wherein the first copolymer comprises about 10 mol%, about 20 mol%, about 30 mol%, about 40 mol%, about 50 mol%, about 60 mol%, about 70 mol%, or about 80 mol% of the first plurality of hydrophobic repeating units.
25. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 5-80 wt% of the plurality of anionic repeating units.
26. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 15-75 wt% of the plurality of anionic repeating units.
27. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 20-50 wt% of the plurality of anionic repeating units.
28. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 10 wt%, about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, about 60 wt%, about 70 wt%, or about 80 wt% of the plurality of anionic repeating units.
29. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 5-80 mol% of the plurality of anionic repeating units.
30. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 15-75 mol% of the plurality of anionic repeating units.
31. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 20-50 mol% of the plurality of anionic repeating units.
32. The composite membrane of any one of claims 1-24, wherein the second copolymer comprises about 10 mol%, about 20 mol%, about 30 mol%, about 40 mol%, about 50 mol%, about 60 mol%, about 70 mol%, or about 80 mol% of the plurality of anionic repeating units.
33. A composite membrane according to any one of claims 1-32, wherein the second copolymer comprises about 10 wt%, about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, about 60 wt%, about 70 wt% or about 80 wt% of the first plurality of hydrophobic repeating units.
34. The composite membrane of any one of claims 1-32, wherein the second copolymer comprises about 10 mol%, about 20 mol%, about 30 mol%, about 40 mol%, about 50 mol%, about 60 mol%, about 70 mol%, or about 80 mol% of the second plurality of hydrophobic repeat units.
35. The composite membrane of any one of claims 1-34, wherein the first copolymer has an average molar mass of at least 30,000 g / mol.
36. The composite membrane of any one of claims 1-37, wherein the first copolymer has an average molar mass of at least 50,000 g / mol.
37. The composite membrane of any one of claims 1-34, wherein the first copolymer has an average molar mass of at least 100,000 g / mol.
38. The composite membrane of any one of claims 1-34, wherein the first copolymer has an average molar mass of 20,000 g / mol to about 500,000 g / mol.
39. The composite membrane of any one of claims 1-34, wherein the first copolymer has an average molar mass of 30,000 g / mol to about 500,000 g / mol.
40. The composite membrane of any one of claims 1-34, wherein the first copolymer has an average molar mass of 50,000 g / mol to about 500,000 g / mol.
41. The composite membrane of any one of claims 1-34, wherein the first copolymer has an average molar mass of 100,000 g / mol to about 500,000 g / mol.
42. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of at least 30,000 g / mol.
43. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of at least 50,000 g / mol.
44. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of at least 100,000 g / mol.
45. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of 20,000 g / mol to about 500,000 g / mol.
46. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of 30,000 g / mol to about 500,000 g / mol.
47. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of 50,000 g / mol to about 500,000 g / mol.
48. The composite membrane of any one of claims 1-41, wherein the second copolymer has an average molar mass of 100,000 g / mol to about 500,000 g / mol.
49. The composite membrane of any one of claims 1-48, wherein the first copolymer and the second copolymer are sequentially layered on the porous support (eg, the first copolymer and the second copolymer are sequentially applied to the porous support).
50. The composite membrane of claim 49, wherein the first copolymer is a first layer (eg, outermost layer) and the second copolymer is a second layer (eg, the first copolymer layer is on the second copolymer layer and the second copolymer layer is in contact with the porous support).
51. The composite membrane of claim 49, wherein the second copolymer is a first layer (eg, an outermost layer) and the first copolymer is a second layer (eg, the second copolymer layer is on the first copolymer layer and the first copolymer layer is in contact with the porous support).
52. The composite membrane of any one of claims 1-48, wherein the first copolymer and the second copolymer are intermixed on the porous support (eg, the first copolymer and the second copolymer form a homogenous layer on the porous support).
53. The composite film of any one of claims 1-52, wherein the first plurality of hydrophobic repeat units comprises repeat units derived from an acrylate (e.g., an alkyl acrylate, a fluorinated acrylate, or a methacrylate), an acrylamide (e.g., a fluorinated acrylamide), styrene, or a hydrophobic amino acid.
54. The composite film of any one of claims 1-52, wherein the first plurality of hydrophobic repeat units comprises repeat units derived from methacrylate.
55. The composite membrane of any one of claims 1-52, wherein the first plurality of hydrophobic repeat units comprises repeat units derived from 2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, pentafluorophenyl methacrylate, styrene, methyl methacrylate, acrylonitrile, 2-chloroethyl methacrylate, 2-bromoethyl methacrylate, and allyl methacrylate.
56. The composite membrane of any one of claims 1-52, wherein the first plurality of hydrophobic repeat units comprises repeat units derived from 2,2-trifluoroethyl methacrylate (TFEMA).
57. The composite film of any one of claims 1-56, wherein the second plurality of hydrophobic repeat units comprises repeat units derived from acrylate (e.g., alkyl acrylate, fluorinated acrylate, or methacrylate), acrylamide (e.g., fluorinated acrylamide), styrene, or a hydrophobic amino acid.
58. The composite film of any one of claims 1-56, wherein the second plurality of hydrophobic repeat units comprises repeat units derived from methacrylate.
59. The composite membrane of any one of claims 1-56, wherein the second plurality of hydrophobic repeat units comprises repeat units derived from 2,2-trifluoroethyl methacrylate (TFEMA), pentafluoropropyl methacrylate, heptafluorobutyl methacrylate, pentafluorophenyl methacrylate, styrene, methyl methacrylate, acrylonitrile, 2-chloroethyl methacrylate, 2-bromoethyl methacrylate, and allyl methacrylate.
60. The composite membrane of any one of claims 1-56, wherein the second plurality of hydrophobic repeat units comprises repeat units derived from 2,2-trifluoroethyl methacrylate (TFEMA).
61. The composite membrane of any one of claims 1-60, wherein the plurality of cationic repeat units comprises repeat units derived from acrylate, acrylamide, styrene, or vinyl monomers substituted with amine, pyridinium, imidazolium, phosphonium, or pyrrolidinium.
62. The composite film of any one of claims 1-60, wherein the plurality of cationic repeat units comprises repeat units derived from methacrylate.
63. A composite membrane according to any one of claims 1-60, wherein the plurality of cationic repeat units comprises repeat units derived from [2-(methacryloyloxy)ethyl]trimethylammonium chloride (MAETA), [3-(methacrylamido)propyl]trimethylammonium chloride, [2-(acryloyloxy)ethyl]trimethylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, 4-vinylbenzyl(triphenyl)phosphonium chloride, methacrylate(vinylbenzyl)trimethylammonium chloride, 3-vinylaniline, 4-vinylaniline, 2-isopropenylaniline, N-(3-aminopropyl)methacrylamide hydrochloride, N-vinylimidazolium, 1-allyl-3-vinylimidazolium, 1-allyl-2-methyl-5-vinyl-pyridinium, 1-allyl-5-vinyl-pyridinium, or 1-methyl-1-(1-vinylcyclohexyl)pyrrolidinium iodide.
64. The composite membrane of any one of claims 1-60, wherein the plurality of cationic repeat units comprises repeat units derived from 2-(methacryloyloxy)ethyl]trimethylammonium chloride.
65. The composite membrane of any one of claims 1-64, wherein the plurality of anionic repeat units comprises repeat units derived from acrylate, acrylamide, styrene, or vinyl monomers substituted with carboxylic acid, sulfonic acid, or phosphoric acid.
66. The composite membrane of any one of claims 1-64, wherein the plurality of anionic repeat units comprises repeat units derived from methacrylate.
67. A composite membrane according to any one of claims 1-64, wherein the plurality of anionic repeating units comprises repeating units derived from methacrylic acid (MAA), 2-sulfoethyl methacrylate (SEMA), L-tryptophan-methacrylamide, D-tryptophan-methacrylamide, L- or D-tryptophan-acrylamide, L- or D-alanine-methacrylamide, L- or D-alanine-acrylamide, L- or D-valine-methacrylamide, L- or D-valine-acrylamide, L- or D-isoleucine-methacrylamide, L- or D-isoleucine-acrylamide, L- or D-alloisoleucine-methacrylamide, L- or D-alloisoleucine-acrylamide, L- or D-methionine-methacrylamide, L- or D-methionine-acrylamide, L- or D-phenylalanine-methacrylamide, L- or D-phenylalanine-acrylamide, L- or D-tyrosine-methacrylamide, L- or D-tyrosine Acid-acrylamide, L- or D-histidine-methacrylamide, L- or D-histidine-acrylamide, L- or D-glutamic acid-methacrylamide, L- or D-glutamic acid-methacrylamide, L- or D-aspartic acid-acrylamide, L- or D-aspartic acid-methacrylamide, acrylic acid, 2-carboxyethyl acrylate, mono-2-(methacryloyloxy)ethyl succinate, mono-2-(methacryloyloxy)ethyl maleate, sodium 4-vinylbenzenesulfonate, 2-Acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt, 2-acrylamido-2-methyl-1-propanesulfonic acid, 3-sulfopropyl acrylate potassium salt, 3-sulfopropyl methacrylate potassium salt, 3-vinylbenzoic acid, 4-vinylbenzoic acid, 2-vinylbenzoic acid, 4-(2-propenyl)benzoic acid, 2-methyl-2-propene-1-sulfonic acid sodium salt, vinylsulfonic acid sodium salt, vinylphosphonic acid or (4-vinylphenyl)methylphosphonic acid.
68. The composite membrane of any one of claims 1-64, wherein the plurality of anionic repeat units comprises repeat units derived from 2-sulfoethyl methacrylate.
69. The composite membrane of any one of claims 1-64, wherein the plurality of anionic repeat units comprises repeat units derived from methacrylic acid.
70. The composite film of any one of claims 1-69, wherein the first copolymer is a statistical (eg, approximately random) copolymer.
71. The composite film of any one of claims 1-69, wherein the first copolymer is a random copolymer.
72. The composite membrane of any one of claims 1-69, wherein the first copolymer is a block copolymer.
73. The composite membrane of any one of claims 1-69, wherein the first copolymer is a graft copolymer or a comb copolymer.
74. The composite film of any one of claims 1-69, wherein the second copolymer is a statistical (eg, approximately random) copolymer.
75. The composite film of any one of claims 1-74, wherein the second copolymer is a random copolymer.
76. The composite membrane of any one of claims 1-74, wherein the second copolymer is a block copolymer.
77. The composite membrane of any one of claims 1-74, wherein the second copolymer is a graft copolymer or a comb copolymer.
78. The composite membrane of any one of claims 1-77, wherein the effective pore size of the composite membrane is smaller than the effective pore size of a membrane prepared by coating only the first copolymer or only the second copolymer on the same porous support.
79. The composite membrane of claim 78, wherein the effective pore size is quantified by measuring the rejection of neutral (eg, uncharged) solutes.
80. The composite membrane of any one of claims 1-79, wherein the first copolymer is cross-linked.
81. The composite film of any one of claims 1-80, wherein the second copolymer is cross-linked.
82. The composite membrane of any one of claims 1-81, wherein the first copolymer and the second copolymer are substantially insoluble in water under operating conditions.
83. The composite membrane of any one of claims 1-81, wherein the first copolymer and the second copolymer are substantially insoluble in water under operating conditions.
84. A method of separating a solute from a solution, the method comprising contacting the solution with a composite membrane according to any one of claims 1-83.
85. The method of claim 84, wherein the solution is passed through (eg, filtered through) the composite membrane.
86. The method of claim 84 or 85, wherein the solute is a salt (eg, sodium chloride).
87. A method for manufacturing a composite membrane according to any one of claims 1-83, the method comprising applying a first copolymer as defined in any one of claims 8-11, 15-24 and 35-41 to a porous support; and applying a second copolymer as defined in any one of claims 11, 12, 25-34 and 42-48, thereby manufacturing a composite membrane according to any one of claims 1-83.
88. The method of claim 87, wherein the first copolymer and the second copolymer are applied sequentially to the porous support layer to form a bilayer membrane.
89. The method of claim 88, wherein the first copolymer is applied first and the second copolymer is then applied.
90. The method of claim 88, wherein the second copolymer is applied first and then the first copolymer is applied.
91. The method of claim 87, wherein the first copolymer and the second copolymer are applied to the porous support layer as a blend (eg, the first copolymer and the second copolymer are mixed prior to application) to form a blended membrane.
92. The method of any one of claims 87-91, wherein the first copolymer is dissolved in a protic solvent (eg, methanol) prior to applying.
93. The method of any one of claims 87-92, wherein the second copolymer is dissolved in a protic solvent (eg, methanol) prior to applying.
94. The method of any one of claims 87-93, wherein the first copolymer and the second copolymer are each dissolved in a protic solvent (eg, methanol) prior to applying.
